2022
DOI: 10.1111/ssqu.13124
|View full text |Cite
|
Sign up to set email alerts
|

Waiting to vote safely: How Covid‐19 safety measures shaped in‐person voter wait times during the 2020 election

Abstract: The aim of this article is to assess the impact of Covid-19 safety measures on voter wait times during the 2020 U.S. election. Methods: Multinomial logistic regression models predicting voter wait times contingent on the presence of Covid safety measures: poll workers wearing face coverings, protective barriers separating voters and workers, voters and booths socially distanced, hand sanitizer, single-use ballot marking pens, and cleaning voting booths between voters, as well as an additive index of these meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…However, feeling safe and being safe are two separate issues, and this evidence should be used in conjunction with that regarding the participatory effects of these policies as well as their efficacy of these mitigation strategies. Regarding participatory effects, other work has noted that Covid policies have the potential to increase voter wait times (Coll, 2022), which may go on to affect voter reneging and turnout (Lamb 2021). Regarding transmission prevention efficacy, previous research has suggested in-person voting may be linked to Covid spread (Cotti et al, 2021) but that some of the policies examined here can limit the spread of Covid in close contact areas such as schools (Kaiser et al, 2021), suggesting they may limit the spread at polling places.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, feeling safe and being safe are two separate issues, and this evidence should be used in conjunction with that regarding the participatory effects of these policies as well as their efficacy of these mitigation strategies. Regarding participatory effects, other work has noted that Covid policies have the potential to increase voter wait times (Coll, 2022), which may go on to affect voter reneging and turnout (Lamb 2021). Regarding transmission prevention efficacy, previous research has suggested in-person voting may be linked to Covid spread (Cotti et al, 2021) but that some of the policies examined here can limit the spread of Covid in close contact areas such as schools (Kaiser et al, 2021), suggesting they may limit the spread at polling places.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that alterations to the in-person voting experience can affect voter wait times (Stein et al, 2020) and that increased wait times decreases voter evaluations of their polling place (Stein & Vonnahme, 2012). Viewed through this lens, Covid safety policies may increase the burden of administering elections, resulting in increased wait times (Coll, 2022) that may go on to decrease voter satisfaction with the operation of their polling place. However, viewed through a ‘safety of polling place operation’ lens rather than a ‘smoothness of polling place operation’ lens, these same policies may increase polling place operation evaluations.…”
Section: Covid-19 Policies and Evaluations Of Election Administrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Coll (2022a) found that among those who voted in person in 2020, polling place safety measures increased perceptions of safety, although it is not clear if those who did not vote in person were aware these measures were in place or would have been made to feel safer by them. Additionally, Coll (2022b) finds that polling place safety measures increased the amount of time people took to vote, suggesting an important potential downside to these measures if the possibility of longer waits decreased turnout.…”
Section: Theoretical Motivation and Prior Literaturementioning
confidence: 99%